Technical Performance Optimization of a Novel Geothermal Hybrid Power Generation System - Zhou, Ying; Qin, Jiyun; Hu, Eric; Zhang, Qinglei (Frontiers in Energy Research, 2022)
Geothermal Aided Power Generation (GAPG) technology is a geothermal hybrid power system that geothermal energy has been integrated into the fossil fired plant to preheat the feedwater, and displace the extraction steam of fossil fired plant. In such a power system, the heat exchange process between extraction steam and geo-fluid occurs in a heat exchange between. When the geo-fluid in the heat exchanger quench to lower temperature for heat transfer purpose, silica scaling would occur in the heat exchanger system. The performance of the GAPG plant would be influenced by the configuration of the heat exchanger and silica scaling in the heat exchanger. For a GAPG plant, it has two possible configurations for a heat exchanger system: series arrangement and parallel arrangement. The different configuration also impacts on the technical performance of the GAPG plant. The silica scaling in the heat exchanger system would harm the performance of the GAPG plant. In this study, a GAPG power system from a 300 MW power plant is used as a case study to understand the impact of displacement selections and heat exchanger arrangement on the performance of the GAPG plant. It was found that there is no silica scaling occurring in heat exchangers system if geo-fluid is used to displace to high-grade extraction steam only. Furthermore, the Parallel arrangement is better than the Series arrangement in terms of the additional power output. Moreover, the GAPG plant has protentional to reduce carbon dioxide emissions by 13%.